Resiliensi Nyobeng Pasca Pandemi Covid-19: Netnografi Pemanfaatan Media Sosial Sebagai Sarana Reaktualisasi Budaya - Widyatama Putra, Zakarias Aria (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Cultural activities following the Covid-19 outbreak have stalled and do not appear to be active again. The establishment of a new order following the epidemic has also had an impact on a variety of economic and social aspects. The study's goal is to discover the type of resilience that Nyobeng exhibits via the usage of social media. This study used the netnography approach to investigate various types of resilience during the Covid-19 epidemic, with the goal of reactivating Nyobeng culture through social media. The Dayak Bidayuh Sebujit tribe conducts community observations and serves as a data source. Data analysis and interpretation of data on websites discussing the usage of social media and the form of Nyobeng resilience following the COVID-19 pandemic are employed, and an iterative technique is used to understand the findings. The research findings are then contrasted to resilience and cultural reactualization theories, as well as policy implications. The study discovered that Nyobeng's resilience after the COVID-19 pandemic has been tested in order to offer information on Nyobeng's implementation after the COVID-19 pandemic in 2023. Instagram and YouTube are also utilised to provide information on Nyobeng's sustainability. Keywords : Resilience, Social Media, Netnography, Cultural Reactualization, Nyobeng